Methodologies to measure the gender dimensions of crime and violence - Shrader, Elizabeth (Policy research working paper, 2001)
The Prevalence rate of violence, as measured by such indicators as domestic assault, homicide, and crime victimization, varies widely locally and worldwide, suggesting that violent behavior is modifiable and preventable. Developing standardized, accurate ways to measure and map violence across communities and countries is the first step toward developing programs to prevent it